An approach to visual interaction analysis of urban spaces. Central Barcelona as a case study. Issue Volume 15:Issues 2(2022) (3rd April 2022) - Clua, Álvaro; Crosas, Carles; Parcerisa, Josep
ABSTRACT: Beyond the binary, traditional, figure-ground reading of urban patterns, this research presents a graduated expression of the geometry of urban spaces from a perceptive point of view. This highlights the spatial relationships and introduces a new set of criteria to evaluate contemporary open spaces according to visual experience. The study produces an innovative reading of central Barcelona by mapping of Visual Clustering Coefficient, one of the parameters derived from the Visual Graph Analysis of isovists.